2022
DOI: 10.3390/molecules27092760
|View full text |Cite
|
Sign up to set email alerts
|

Delving into the Therapeutic Potential of Carica papaya Leaf against Thrombocytopenia

Abstract: Thrombocytopenia is a clinical manifestation that refers to the low platelet count, i.e., <150 × 103/μL, of blood, resulting in imbalanced hemostasis, which leads to several fatal complications. The causative factors vary greatly, but, as a consequence, they interfere with platelet production and promote destruction, leading to death. Carica papaya leaf has unique therapeutic and medicinal characteristics against thrombocytopenia, and this is supported by scientific studies. Secondary metabolites and minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…This result is by a recent study which shows that platelet counts significantly increased in patients with dengue fever and dengue hemorrhagic fever treated with Carica papaya leaves extract [18] ; this is a result of its immunomodulatory effect [38], as reported in another study which shows that it was able to mediate allergic reactions and inhibit the growth of certain tumor cells, the leaves contains flavonoids, a potent antioxidant, alpha-tocopherol, and benzyl isothiocyanate, which increases the production of Th1-type cytokines [39]. Another study revealed that the leaf extract showed a significant therapeutic effect on Thrombocytopenia, a clinical manifestation of low platelet count [40]; this is also in line with our result.…”
Section: Discussionmentioning
confidence: 94%
“…This result is by a recent study which shows that platelet counts significantly increased in patients with dengue fever and dengue hemorrhagic fever treated with Carica papaya leaves extract [18] ; this is a result of its immunomodulatory effect [38], as reported in another study which shows that it was able to mediate allergic reactions and inhibit the growth of certain tumor cells, the leaves contains flavonoids, a potent antioxidant, alpha-tocopherol, and benzyl isothiocyanate, which increases the production of Th1-type cytokines [39]. Another study revealed that the leaf extract showed a significant therapeutic effect on Thrombocytopenia, a clinical manifestation of low platelet count [40]; this is also in line with our result.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, recent studies explain how PC positively affect certain illnesses, such as obesity, diabetes, cardiovascular diseases, thrombocytopenia, or metabolic syndrome [ 1 , 8 , 9 ]. Several common features characterize these pathologies; among them, we can highlight the redox balance and a notable inflammatory response that strongly alters the biochemical and functional characteristics of the affected tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaloid carpaine in carica papaya leaves has displayed antithrombocytopenic activity in many researches 11 . Carpaine and quercitin in papaya leaves promotes platelet production, inhibits platelet damage and maintains platelet membrane via gene expression activity and ceasing of viral proteases, respectively 12 .The papain enzyme has also been reported to reverse immune mediated platelet destruction 13 . The current literature shows that Carica papaya leaf juice augments platelet activity.…”
Section: Introductionmentioning
confidence: 99%